Timing of TIAs preceding stroke: time window for prevention is very short. - Rothwell, P; Warlow, C (2005)
BACKGROUND: Patients with TIA are at increased risk of ischemic stroke and require preventive treatment. However, clinical guidelines differ on how urgently patients should be assessed. OBJECTIVE: To determine the potential consequences of delays in investigation and treatment, the authors studied the timing of TIAs preceding ischemic stroke. METHODS: The authors studied patients who presented with a recent ischemic stroke and had a preceding TIA in two population-based studies (Oxford Vascular Study [OXVASC]; Oxfordshire Community Stroke Project [OCSP]) and two randomized trials (UK TIA Aspirin Trial [UK-TIA]; European Carotid Surgery Trial [ECST]). RESULTS: Of 2,416 patients who had presented with an ischemic stroke, 549 (23%) gave a history of a preceding TIA (18% in OXVASC, 15% in OCSP, 23% in UK-TIA, 26% in ECST). Where a preceding TIA had occurred, the timing was highly consistent across the studies, with 17% occurring on the day of the stroke, 9% on the previous day, and 43% at some point during the 7 days prior to the stroke. No clinical characteristics or vascular risk factors identified patients in whom there was a close temporal association between TIA and stroke. CONCLUSION: In patients presenting with ischemic stroke, TIAs occur most often during the hours and days immediately preceding the stroke.